The impact of school-based financial education on high school students and their teachers: Experimental evidence from Peru - Verónica Frisancho Robles (Inter-American Development Bank (IDB), 2018)
Using data from a randomized controlled trial in 300 public high schools in Peru, this paper studies the potential of school-based financial education programs for youth. The intervention improves students' and teachers' financial knowledge by 0.14 SD and 0.32 SD, respectively. The impact of the intervention also extends to socioemotional traits and behavior, as sizable positive impacts on self-control and consumption habits among students are identified. Teachers in the treatment group become more impulsive and risk averse, and they are more likely to save (9 percentage points) and to save formally (14 percentage points).
Keywords: D14; D91; J24; O16; 330; Financial education; Youth; Self-Control; Consumption behavior; Savings; Treatment effects